2016
DOI: 10.1016/j.enpol.2016.03.013
|View full text |Cite|
|
Sign up to set email alerts
|

Get rid of it: To what extent might improved reliability reduce self-generation in Nigeria?

Abstract: Despite the global concerns surrounding the threats of climate change to both human health and sustainable environments, gasoline-or diesel-powered generators with non-negligible emissions have become a popular choice among Nigerian households due to the poor publicly provided electricity. This study examines the extent to which an improvement in publicly supplied electricity may reduce backup generation and, by implication, reduce emissions from Nigerian homes. The results from a random-effects probit analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The small gasoline generator market is believed to be in about 22 million in 2018 and is projected to increase to 30 million by 2030 ( Oseni, 2016 ; Adeniran et al., 2017 ; Dalberg, 2019 ). Dalberg (2019) also reported that about $12 billion was expended on importation, fuelling, repair and maintenance of generators in 2018.…”
Section: Drivers Of Anthropogenic Air Pollutants In Nigeriamentioning
confidence: 99%
“…The small gasoline generator market is believed to be in about 22 million in 2018 and is projected to increase to 30 million by 2030 ( Oseni, 2016 ; Adeniran et al., 2017 ; Dalberg, 2019 ). Dalberg (2019) also reported that about $12 billion was expended on importation, fuelling, repair and maintenance of generators in 2018.…”
Section: Drivers Of Anthropogenic Air Pollutants In Nigeriamentioning
confidence: 99%
“…There are multiple sources of ambient PM 2.5 pollution in Lagos. Anthropogenic sources include road transport [30], power generators [31] [32], poor waste management due to open dumpsites and illegal burning of waste [33], and construction industry [34]. In addition, natural sources, such as dust and sea salts, are also known to be significant [35].…”
Section: Ambient Pm 25 Pollution In Lagosmentioning
confidence: 99%
“…Traditionally, solar use has been limited in the country, with existing literature revealing its use, primarily on small scale and isolated applications in rural areas for residential and community use (Sambo, 2010), as well as, one-off independent use by private individuals and government (Oseni, 2016). However, its level of adoption in commercial buildings is not known (Onyekuru and Marchant, 2012;Arup Nigeria, 2016).…”
Section: Introductionmentioning
confidence: 99%